Gut mediated syncope - Azevedo, Pedro (2019)
Gastrointestinal stromal tumor (GIST) is a rare mesenchymal tumor (0,3-3% of all gastrointestinal tumors), mostly found in the stomach and small intestine. In most cases, GIST is caused by a gain-of-function mutation in KIT gene, resulting in an abnormal proliferation of interstitial Cajal cells. We report the case of a 74-year-old man, with a history of ischemic heart disease, under double antiaggregation, who went to the hospital after an episode of syncope. Physical examination was unremarkable, and his exams only revealed an iron deficiency anemia (9.2 g/dL). Subsequent diagnostic investigation showed a colon adenoma that was excised endoscopically. He presented a new episode of syncope, associated with acute hemoglobin decrease (4.5 g/dL), without clinical evidence of blood loss. We repeated the studies (endoscopic and tomography), which were negative. In the meantime, a videocapsule study was performed, which found a mass in the jejunum, surgically excised, confirming the diagnosis of GIST; the true cause of anemia and syncope. One year passed, our patient is taking imatinib, with no evidence of relapse. Presenting this case report, we do a brief review of this theme. The diagnosis of GIST is not always linear. They are manifested mainly by gastrointestinal hemorrhage and anemia, and most are detected in endoscopic examinations or by computed tomography. Whenever possible, complete surgical resection is the treatment of choice, with adjunctive treatment with imatinib in high-risk patients. In the presence of an unresectable GIST or whose excision may result in great morbidity, imatinib may also be used as neoadjuvant. In advanced metastatic disease, treatment is only done with tyrosine-kinase inhibitors, and surgery is done only for some of the complications.